Validity of a mobile device measuring isometric deadlift peak force - Alain Dössegger; Konrad Brügger (Bern Open Publishing, 2023)
Introduction Muscular strength can be viewed as a product of force and velocity. Increases in both maximal force and velocity will ultimately result in an increase in power (Suchomel et al., 2016), thus contributing to performance in tasks such as athletic competition or police and military special operations. Testing isometric peak force is a reliable method to assess maximal strength (De Witt et al., 2018). Isometric mid-thigh pull tests and squat tests in various knee- and hip angles are well known. These tests, however, require force plates with computer and software, as well as a barbell that disallows displacement of the bar (usually a heavy equipment). Decentralized testing requires a reliable, lightweight and mobile measurement device comparable to standard isometric tests as described elsewhere (Maier et al., 2016). Therefore, a tension gauge (load cells) was attached to a board and a handle to perform isometric sumo stance deadlifts. The question is whether the mobile device produces comparable results to maximal isometric strength tests on force plates. Method Correlation analysis (Bayesian Pearson's rho, Prior~Beta 1,1) and Equivalence Bayesian Paired Samples T-Tests (Lakens, 2017; Prior~Cauchy 0,0.707, a priori Limits of Agreement = +/-5%) of the measurements from the mobile test device and from force plates (CYCCESS) were performed using JASP Version 0.14.1. Healthy, trained subjects (n = 12) volunteered to perform maximal isometric deadlifts on each test device. Results were validated by additional 6 pairs of lifts on each device. Results Pearson's rho was 0.969 (95% credible interval of the posterior distribution 0.824, 0.993). After adjusting the measures of the mobile device for the offset (mean of the differences of 416 N), Bayes factor favoring the hypothesis that the effect size lies inside the interval of +/-5% was 3.006. The additional measurements confirmed the substantial evidence for equivalence of the two measurements. Discussion Isometric tests are relatively simple, safe and time efficient to administer and possess high degrees of reliability (Grgic et al., 2022). The strong relationship between isometric peak force and deadlift 1RM (De Witt et al., 2018) makes them a valuable tool for exercise prescription. Our lightweight, mobile test device offers high precision (technical measurement error of the load cells = 0.5%) and safe testing procedure. Concurrent validity, as well as face validity, seems to be reasonably high: measurements with the mobile device do not differ from a isometric deadlift test on force plates, and lifting casualties and heavy loads could be well represented by force produced from the floor position (Bartolomei et al., 2022). References Bartolomei, S., Rovai, C., Lanzoni, I. M., & di Michele, R. (2022). Relationships between muscle architecture, deadlift performance, and maximal isometric force produced at the midthigh and midshin pull in resistance-trained individuals. Journal of Strength and Conditioniung Research, 36(2), 299-303. https://doi.org/10.1519/jsc.0000000000003455 De Witt, J. K., English, K. L., Crowell, J. B., Kalogera, K. L., Guilliams, M. E., Nieschwitz, B. E., Hanson, A. M., & Ploutz-Snyder, L. L. (2018). Isometric midthigh pull reliability and relationship to deadlift one repetition maximum. The Journal of Strength and Conditioning Research, 32(2), 528-533. https://doi.org/10.1519/jsc.0000000000001605 Grgic, J., Scapec, B., Mikulic, P., & Pedisic, Z. (2022). Test-retest reliability of isometric mid-thigh pull maximum strength assessment: A systematic review. Biology of Sport, 39(2), 407-414. https://doi.org/10.5114/biolsport.2022.106149 Lakens, D. (2017). Equivalence tests: A practical primer for t tests, correlations, and meta-analyses. Social Psychological and Personality Science, 8(4), 355-362. https://doi.org/10.1177/1948550617697177 Maier, T., Gross, M., Trösch, S., Steiner, T., Müller, B., Bourban, P., Schärer, C., Hübner, K., Wehrlin, J., Tschopp, M., Wilhelm, M., Clenin, G. E., Züst, P., & Seidel, R. (2016). Manual Leistungsdiagnostik [Performance diagnostics manual]. http://www.swissolympic.ch/Portaldata/41/Resources/03_sport/00_dokumente/Manual_Leistungsdiagnostik_(letzte_Aenderung_01.02.2016).pdf Suchomel, T. J., Nimphius, S., & Stone, M. H. (2016). The importance of muscular strength in athletic performance. Sports Medicine, 46(10), 1419-1449. https://doi.org/10.1007/s40279-016-0486-0